2022
DOI: 10.3389/fpsyt.2021.570971
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress and Psychological Impact Among Healthcare Workers at a Tertiaty Hospital in China During the COVID-19 Outbreak: The Moderating Role of Resilience and Social Support

Abstract: AimsTo investigate the psychological distress experienced by healthcare workers (HCWs) at a tertiary hospital in Changzhou, China, outside Wuhan, during the early stage of COVID-19 and evaluate the moderating effects of resilience and social support on the relationship between stress and psychological distress.MethodsThe study was conducted between February 10 and 15, 2020, in a non-probabilistic way. The survey included questions regarding the risk of exposure, sociodemographics, perceived stress [10-item Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Hence, in the case of the COVID-19 pandemic, not only stress is increased, but resilience is decreased. The supportive relationships that normally support the buffering of stress [133][134][135] have now become a source of stress themselves, as they are disrupted by the COVID-19 mitigation measures [136]. Furthermore, the stress resulting from interpersonal stress and increased exposure to domestic violence [103,137], which is increased during the COVID pandemic, is especially detrimental to fetal development, as is reflected in increased risk of preterm birth and low birth weight [138].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, in the case of the COVID-19 pandemic, not only stress is increased, but resilience is decreased. The supportive relationships that normally support the buffering of stress [133][134][135] have now become a source of stress themselves, as they are disrupted by the COVID-19 mitigation measures [136]. Furthermore, the stress resulting from interpersonal stress and increased exposure to domestic violence [103,137], which is increased during the COVID pandemic, is especially detrimental to fetal development, as is reflected in increased risk of preterm birth and low birth weight [138].…”
Section: Discussionmentioning
confidence: 99%
“…HCPs were given the Italian version of validated questionnaires described thereinafter, which are also commonly used in HCP cohorts [ 18 , 19 , 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In our systematic review, it was shown that nursing students were able to cope with clinical environment as they use different coping strategies. It was also shown in one previous study that coping and social support control the stress level among healthcare providers during the COVID-19 pandemic [33].…”
Section: Discussionmentioning
confidence: 81%